2005
DOI: 10.2172/15020675
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Flux of Fish in the Forebay of The Dalles Dam in 2003

Abstract: In spring and summer 2003, the Pacific Northwest National Laboratory led a team that conducted mobile and fixed hydroacoustic surveys in the forebay of The Dalles Dam for the U.S. Army Corps of Engineers-Portland District. This research was part of the Corps' Anadromous Fish Evaluation Program. The surveys provided information on the distribution and movement of smolt-sized fish relative to ambient factors such as flow, bathymetry, or diel cycle in the forebay at The Dalles Dam. A proposal for the use of a gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In addition, the mean depths of yearling Chinook salmon ranged from 1.5 m in the Snake River to 3.2 m near the forebay of McNary Dam (the range in upper and lower 95% confidence intervals was 1.3-3.6 m). Faber et al (2005) observed suspected juvenile yearling and subyearling Chinook salmon and steelhead in the upper 6.1 m of the water column in the forebay of the Dalles Dam, but it was not uncommon to observe them at depths of 12.2 m in the forebays of Columbia River dams (Faber et al 2001). Similar depths for juvenile salmonids were observed by Dauble et al (1989) in the Hanford Reach of the Columbia River.…”
Section: Factors Associated With Mortal Injurysupporting
confidence: 75%
“…In addition, the mean depths of yearling Chinook salmon ranged from 1.5 m in the Snake River to 3.2 m near the forebay of McNary Dam (the range in upper and lower 95% confidence intervals was 1.3-3.6 m). Faber et al (2005) observed suspected juvenile yearling and subyearling Chinook salmon and steelhead in the upper 6.1 m of the water column in the forebay of the Dalles Dam, but it was not uncommon to observe them at depths of 12.2 m in the forebays of Columbia River dams (Faber et al 2001). Similar depths for juvenile salmonids were observed by Dauble et al (1989) in the Hanford Reach of the Columbia River.…”
Section: Factors Associated With Mortal Injurysupporting
confidence: 75%
“…In an effort to improve survival of spilled fish, a wall dividing the spillway between Bays 6 and 7 was installed prior to the 2004 juvenile salmonid migration season and a bulk spill pattern at Bays 1-6 was adopted. Bioengineering is currently underway to design a floating wall in the forebay to divert juvenile salmonids from the powerhouse to the spillway; this effort is applying results from forebay distribution and migration pathway studies by Cash et al (2005) and Faber et al (2005). At the sluiceway, an alternative means of operating the entrance gates may provide additional protection for juvenile salmonids at the TDA powerhouse.…”
Section: Introductionmentioning
confidence: 99%
“…• Fixed and mobile hydroacoustic survey techniques for fish assessment are well established (Burczynski 1979;MacLennan and Simmonds 1992;Faber et al 2005;Stables et al 2005). A boat surveys for fish as it moves from station to station across the impact area.…”
Section: Exposure-response Assessment Techniquesmentioning
confidence: 99%